AUDITORÍA FINANCIERA AL GOBIERNO AUTÓNOMO DESCENTRALIZADO PARROQUIAL DE MALACATOS DEL CANTÓN Y PROVINCIA DE LOJA, PERÍODO 2015 - Sarango Armijos, Karla Stefania (2017)
The thesis work entitled "FINANCIAL AUDIT TO THE DECENTRALIZED AUTONOMOUS GOVERNMENT OF MALACATOS DEL CANTÓN AND PROVINCE OF LOJA, PERIOD 2015" was oriented to meet the objectives set that refer to: Evaluate the internal control system implemented by the Decentralized Parochial Autonomous Government Of Malacatos, was made through the visit to the Autonomous Government Decentralized Parish, interviews were made to the president and the staff that works in the accounting area; We also compiled and analyzed the information of supporting documents, the internal control questionnaire was elaborated, which allowed to evaluate, to qualify the level of risk and confidence of each component, we identify the findings with respective evidences and backups in which it can be evidenced that The entity is complying with the internal control standards issued by the Comptroller General of the State. The second objective refers to the application of techniques and procedures to determine the reasonableness of the financial statements that were complied with through the application of analytical and summary certificates where it was verified that the balances of the audited components are reasonable, the records of The transactions have been carried out in a timely manner, and the respective documentation has been revised as a journal, general ledger, invoices and documents that serve as an 5 endorsement of the economic movements that affect the financial situation of the entity. The third objective refers to the preparation of the audit report, which has been complied with through the drafting of the cover letter followed by the presentation of the results obtained from the examination carried out to the entity, which contain the findings obtained with their respective Comments, conclusions and recommendations, which are reflected in the audit report, which will serve the authorities of the parish GAD of Malacatos, to improve the internal control of economic and financial operations. Among the principal findings determined in the audit, the entity does not perform the monthly reconciliations of its bank accounts, the respective cash balances are not made, in the fixed assets there are smaller assets, the payments are not made in a timely manner, there is no A segregation of functions and the supporting documents are not in a safe and well ordered place so it is recommended to carry out an annual financial audit to evidence the reasonableness of accounting balances and to take efficient corrections and in time to improve The accounting - financial administration of the institution